Introductory notes to comparative law - Sotomarino Cáceres, Roxana (2018)
Comparative Law like a method or “meta-method” has an especial relevance in legal analysis and production, especially in a globalized world. The utility of comparative analysis between different figures from two or more legal families using different elements to this analysis, such as legal elements, historic, politic and others is undeniable.In this article, the author present us the Comparative law from different edges to show its development, importance and state in our days.